Proposta de método para análise de qualidade ambiental e humanização em maternidades. Estudo de caso: Maternidade Nascer Cidadão - Goiânia - Brasil - Cotrim, Nayara Araújo de Assis (2019)
The public hospital, as health care equipment (EAS), is an equipment that has relevance in the context of the city because it is directly related to the health of the human being, being one of the public equipment most used by the population, which must have direct access, where necessary, to this equipment. Maternity is the part of the public health system responsible for women's health and delivery. It must be endowed with spatial and architectural quality, ensuring that pregnant women and their families find in this public equipment all the necessary quality for a good care from the screening and preparation for delivery to the evaluation of the baby and the postpartum mother. This dissertation aimed to understand, analyze and diagnose maternity through a specific method. For a case study, the Nascer Cidadão maternity hospital, located in the city of Goiânia, was chosen and analyzed. In order to collect data related to environmental comfort and humanization, a method was developed with a specific questionnaire for maternity hospitals, which was called MAVQAHM (Method of Environmental Quality Assessment and Humanization for Maternities) to be filled by the various users of this space. by the researcher. The method was elaborated based on the AEDET (Achieving Excellence Design Evaluation Toolkit) method and the data obtained by the MAVQAHM method were analyzed by the Net Promoter Score (NPS) method. The questionnaire, gave rise to a diagnosis of the maternity case study, demonstrating that the areas related to safety, urban and social integration, and performance, are the ones that have the largest gap, from the perspective of users. From the diagnosis, the public power and the direction of maternity, has a study that supports and directs possible and future interventions in the preexisting building, as well as substrate, through the elaborated method, to guide and direct future projects of maternity in the city of Goiânia.